Odpowiedź :
Cześć!
Obliczenia
[tex]\frac{2\sqrt2}{4+\sqrt3}=\frac{2\sqrt2}{4+\sqrt3}\cdot\frac{4-\sqrt3}{4-\sqrt3}=\frac{2\sqrt2(4-\sqrt3)}{(4+\sqrt3)(4-\sqrt3)}=\frac{8\sqrt2-2\sqrt6}{4^2-(\sqrt3)^2}=\frac{8\sqrt2-2\sqrt6}{16-3}=\frac{8\sqrt2-2\sqrt6}{13}\\[/tex]
W mianowniku wykorzystałam wzór skróconego mnożenia
[tex](a+b)(a-b)=a^2-b^2[/tex]
Odpowiedź:
[tex] \frac{2 \sqrt{2} }{4 + \sqrt{3} } = \frac{2 \sqrt{2} }{4 + \sqrt{3} } \times \frac{4 - \sqrt{3} }{4 - \sqrt{3} } = \frac{(2 \sqrt{2})(4 - \sqrt{3}) }{ {4}^{2} - { \sqrt{3} }^{2} } = \frac{8 \sqrt{2} - 2 \sqrt{6} }{16 - 3} = \frac{8 \sqrt{2} - 2 \sqrt{6} }{13} [/tex]